Ontological manifestations of trust for service oriented environment - Hussain, Farookh; Chang, Elizabeth; Dillon, Tharam S. (IEEE Computer Society Press, 2006)
Trust and Reputation are vital components for trusted e-business. In the literature however there has been no effort in proposing ontology for trust. The trusted agent in service oriented environment may trust a software agent or human agent or a service or a product. Based on this distinction, trust ontology could be proposed for different domains. The trust ontology for the individual domains is proposed and discussed.